2020
DOI: 10.1101/2020.09.03.281923
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Subcutaneous nanotherapy repurposes the immunosuppressive mechanism of rapamycin to enhance allogeneic islet graft viability

Abstract: Rapamycin is an orally administered immunosuppressant that is plagued by poor bioavailability and a wide biodistribution. Thus, this pleotropic mTOR inhibitor has a narrow therapeutic window, a wide range of side effects and provides inadequate transplantation protection. Here, we demonstrate that subcutaneous rapamycin delivery via poly(ethylene glycol)-b-poly(propylene sulfide)) (PEG-b-PPS) polymersome (PS) nanocarriers modulates the cellular biodistribution of rapamycin to change its immunosuppressive mecha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…21,22,37 These systems have been extensively studied in terms of their sustained drug release kinetics, toxicity, and cell uptake both in vitro and in vivo. 22,30,39 In our previous study, we showed that an anti-integrin (anti-αvβ3) SDV heptapeptide bound to PEG-b-PPS MCs could efficiently inhibit angiogenesis with less peptide concentration in micellar form compared to the bare peptide. 37 This demonstrated the new approach where the targeting ligand can act as therapeutic moiety as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22,37 These systems have been extensively studied in terms of their sustained drug release kinetics, toxicity, and cell uptake both in vitro and in vivo. 22,30,39 In our previous study, we showed that an anti-integrin (anti-αvβ3) SDV heptapeptide bound to PEG-b-PPS MCs could efficiently inhibit angiogenesis with less peptide concentration in micellar form compared to the bare peptide. 37 This demonstrated the new approach where the targeting ligand can act as therapeutic moiety as well.…”
Section: Discussionmentioning
confidence: 99%
“…The PEG‐ b ‐PPS block‐copolymer is a versatile delivery platform that can self‐assemble into thermodynamically stable structures like MCs, polymersomes, and filomicelles 21,22,37 . These systems have been extensively studied in terms of their sustained drug release kinetics, toxicity, and cell uptake both in vitro and in vivo 22,30,39 . In our previous study, we showed that an anti‐integrin (anti‐αvβ3) SDV heptapeptide bound to PEG‐ b ‐PPS MCs could efficiently inhibit angiogenesis with less peptide concentration in micellar form compared to the bare peptide 37 .…”
Section: Discussionmentioning
confidence: 99%
“…8 They synthesized a MECA79 monoclonal antibody (mAb)-coated NP that carries an anti-CD3 payload (MECA79-anti-CD3-NP). MECA-79-anti-CD3-NPs 15 Rapamycin is a potent immunosuppressive drug and, yet, is not readily used in the perioperative period due to a host of adverse side effects when administered systemically. 16 By encapsulating rapamycin in PS nanocarriers, rPS achieved antigen-specific tolerance for transplanted pancreatic islets in a major histocompatibility complex (MHC)-mismatched, allogeneic, intraportal (liver) transplantation model during the treatment of type I diabetes.…”
Section: Bahmani Et Al Reported On a Novel Intravascular Delivery Plat-mentioning
confidence: 99%
“…Typically, an immunosuppressive agent is encapsulated inside the NP, and cell or tissue targeted delivery is achieved by conjugating antibodies or aptamers or peptides or cyclic peptides on the surface of the NPs. Some examples of each NP developed and/or tested for transplantation are shown 8,9,12,14,15,[31][32][33][34] | 1295 AJT PLUMBLEE Et aL.…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation